2022
DOI: 10.1021/acs.jmedchem.2c00505
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of a Synthetic Class of Nectin-4-Targeted CD137 Agonists for Immuno-oncology

Abstract: CD137 (4-1BB) is a co-stimulatory receptor on immune cells and Nectin-4 is a cell adhesion molecule that is overexpressed in multiple tumor types. Using a series of poly(ethylene glycol) (PEG)-based linkers, synthetic bicyclic peptides targeting CD137 were conjugated to Bicycles targeting Nectin-4. The resulting bispecific molecules were potent CD137 agonists that require the presence of both Nectin-4-expressing tumor cells and CD137-expressing immune cells for activity. A multipronged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This is the third reported example of high-affinity and selective tumor-targeting Bicycles being employed in toxin conjugates to give potent and well-tolerated anticancer agents, ,, further demonstrating that this approach is generalizable and has the potential to generate a pipeline of such compounds for targeted cancer therapy. In addition, Nectin-4 targeting Bicycles have been employed in fully synthetic, Nectin-4 targeting immune cell agonists (TICAs), which induce tumor-localized CD137 agonism and show robust antitumor activity in preclinical in vivo studies. ,, Tumor-targeting Bicycles can be utilized as delivery moieties for a variety of payloads and have the potential to generate a diverse range of oncology medicines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the third reported example of high-affinity and selective tumor-targeting Bicycles being employed in toxin conjugates to give potent and well-tolerated anticancer agents, ,, further demonstrating that this approach is generalizable and has the potential to generate a pipeline of such compounds for targeted cancer therapy. In addition, Nectin-4 targeting Bicycles have been employed in fully synthetic, Nectin-4 targeting immune cell agonists (TICAs), which induce tumor-localized CD137 agonism and show robust antitumor activity in preclinical in vivo studies. ,, Tumor-targeting Bicycles can be utilized as delivery moieties for a variety of payloads and have the potential to generate a diverse range of oncology medicines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Nectin-4 targeting Bicycles have been employed in fully synthetic, Nectin-4 targeting immune cell agonists (TICAs), which induce tumor-localized CD137 agonism and show robust antitumor activity in preclinical in vivo studies. 16 , 24 , 25 Tumor-targeting Bicycles can be utilized as delivery moieties for a variety of payloads and have the potential to generate a diverse range of oncology medicines.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional analysis has shown that Nectin-4 and CD137 are co-expressed in a variety of cancers. BT7480 targets Nectin-4-expressing tumor cells and then binds to and agonizes CD137 on nearby immune cells to remodel the tumor immune microenvironment, thereby eliminating tumor cells and inhibiting tumor recurrence ( 115 , 116 ). Compared with CD137 activation alone, immune killing after targeted activation shows a better therapeutic effect and less liver toxicity.…”
Section: Oncological Therapeutic Value Of Nectin-4mentioning
confidence: 99%
“…After in vitro proof-ofconcept, linker selection and valence optimization, the researchers obtained BT7480 (Fig. 6) [79]. By linking two bicyclic peptides through PEG chains, the newly obtained bicyclic peptide conjugates can act on two target proteins simultaneously, effectively activate CD137 and exert anti-tumor effects.…”
Section: Bicyclic Peptides In Clinical Trialsmentioning
confidence: 99%